(untitled) (International Journal of Physiotherapy, 2020)
Background: Participation in sports positively related to the usage of sports facilities. Participation in sports becomes an indicator of the active lifestyle of Malaysians. Ministry of Youth and Sports defines sports culture as sports activities, exercise, and active recreational activities which become practices and routine towards an active, energetic, and competitive lifestyle. (IYRES, 2019). Sports facilities are places for sports activities such as stadiums, halls, fields, courts, and support facilities, including the parking area and cafes. The trend in using sports facilities, exercise, and active recreation vary from one another. Sports activities depend much on a sports facility’s specific, while exercise and recreation activities don’t necessarily need a specific sports facility. Methods: The survey of the Malaysian Sports Culture Index was done in 2019 among 8468 Malaysian from 13 years and above according to gender, age, locality, marital status, and ethnicity. The data collected through the questionnaire developed by the Malaysian Institute for Youth Research (IYRES). Results: Descriptive analysis showed that the overall facility usage is at a low level of 46.9 according to the IYRES (2018) norm. This means efforts are needed to encourage sports facilities to increase the score to a higher level. Further analysis shows that people’s main choice for sports activities is multipurpose halls and public facilities 39.3%. Malaysians chose residential areas to exercise (27.9%) and for recreational activities (32.1%). Gender, age, and marital status influence facilities’ usage, but locality and ethnicity don’t. Conclusion: In conclusion, people who are active in sports need specific sports facilities, while those active in exercise and recreation require only public amenities appropriate to the type of activities carried out around residential areas.